The Role of School Culture and Progressive Leadership in Promoting Innovative Learning in the Era of the Fourth Industrial Revolution: A Study in Integrated Islamic Schools in West Java - Subasman, Iman (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2023)
Purpose – This research aims to investigate, identify, and analyze the factors of school culture that support or hinder the implementation of innovative learning methods and their impact on learning effectiveness in facing the challenges of the Fourth Industrial Revolution era Design/methods/approach – Adopting a qualitative methodology with an ethnographic approach, this study collected data through in-depth interviews, literature review, documentation studies, and direct observations in several schools with an Islamic background in West Java. Data analysis was conducted inductively to identify emergent themes. Findings – The study results indicate that progressive leadership and a school culture that supports innovation play a crucial role in enhancing student engagement and the effective use of educational technology. Conversely, a conservative school culture and limited resources were the main barriers to adopting innovative learning methods. This study also found that changes in norms, values, and school practices that support innovation and change are essential for effective education transformation. Research implications – These findings provide valuable insights for policymakers, educational practitioners, and school leaders about the importance of school culture and leadership in designing and implementing innovative learning strategies. This research emphasizes the need for a holistic and inclusive approach to education, considering cultural and leadership aspects to maximize the effectiveness of innovative learning. Recommendations for future research include using more diverse approaches to expand understanding of the dynamics between school culture, leadership, and educational innovation.